Investigating the dynamic responses of Aegilops tauschii Coss. to salinity, drought, and nitrogen stress: a comprehensive study of competitive growth and biochemical and molecular pathways - Hameed, Rashida; Abbas, Adeel; Saeed, Muhammad; Shahani, Aitezaz A. A.; Huang, Ping; Du, Daolin; Zulfiqar, Usman; Alamri, Saud; Alfagham, Alanoud T. (Frontiers in Plant Science, 2023)
Aegilops tauschii (Coss.) is a highly deleterious, rapidly proliferating weed within the wheat and its DD genome composition exhibits adaptability towards diverse abiotic stresses, demonstrates heightened efficacy in nutrient utilization. Current study investigated different variegated impact of distinct nitrogen concentrations with varied plant densities, scrutinizing the behaviour of Ae. tauschii under various salinity and drought stress levels through multiple physiological, bio-chemical, and molecular pathways. Different physiological parameters attaining high growth with different plant density and different nitrogen availability increased Ae. tauschii dominancy. Conversely, under the duress of salinity and drought, Ae. tauschii showcased enhanced performance through a comprehensive array of physiological and biochemical parameters, including catalase, peroxidase, malondialdehyde, and proline content. Notably, salinity-associated traits such as sodium, potassium, and the sodium potassium ratio exhibited significant variations and demonstrated remarkable tolerance capabilities. In the domain of molecular pathways, the HKT and DREB genes have displayed a remarkable upregulation, showcasing a comparatively elevated expression profile in reaction to different levels of salinity and drought-induced stress. Without a doubt, this information will make a substantial contribution to the understanding of the fundamental behavioral tendencies and the efficiency of 2 This is a provisional file, not the final typeset article nutrient utilization in Ae. tauschii. Moreover, it will offer innovative viewpoints for integrated management, thereby enabling the enhancement of strategies for adept control and alleviation.